Complex multi-step martensitic twinning process during plastic deformation of the superelastic Ti-20Zr-3Mo-3Sn alloy. (1st September 2022) - Gao, J.J.; Castany, P.; Gloriant, T.
Abstract: The Ti-20Zr-3Mo-3Sn (at.%) alloy is investigated before and after deformation by conventional and cyclic tensile tests, electron back-scattered diffraction (EBSD), in situ synchrotron X-ray diffraction (SXRD) and transmission electron microscopy (TEM). On one hand, the maximum recovery strain of 3.3% is obtained, which is attributed to the favorable {111}<101>β texture of β phase after short solution treatment. On the other hand, plastic deformation mechanisms are studied from specimens strained to 5% and 8%. The reversible stress-induced martensitic (SIM) α" transformation is preliminary detected by SXRD during loading and after unloading in both specimens. Then, the deformation microstructures are further investigated in details by TEM. At 5% of strain, primary α" deformation bands are observed with an abnormal orientation relationship (OR) with β phase. From crystallographic reconstruction, this OR is shown to be due to {130}<310>α" twinning followed by {111}α″ type Ⅰ reorientation twinning during loading. At 8% of strain, a complex hierarchical microstructure composed of primary and secondary α" bands is observed, which corresponds to residual primary {130}<310>α" twins with secondary {130}<310>α" twins occurring after {111}α″ reorientation twinning of primary {130}<310>α" twins. The sequence of plastic deformation is then composed of primary {130}<310>α" twinning, followed by {111}α″ reorientation twinning and finally secondary {130}<310>α" twinning. A thin layer of ω phase is also observed at the β/α" inter-phase boundary. Occurrence of this unprecedented complex multi-step martensitic twinning process is rationalized by means of Schmid factor analysis and transformation strain calculations. Graphical abstract: Image, graphical abstract